Balaghah as an instrument of Qur'an interpretation: a study of al-Kashshaf - Zubir, Badri Najib (IIUM Press, 2008)
This book shows that in balaghah, or the science of rhetoric, there are theories and principles which could help a reader of the Qur'an achieve a better understanding of its message because they specify certain things to look for in a text and provide procedures for making sense of why they are there. It recognizes that sometimes, for the sake of communicating a particular meaning, the rules of grammar are defied. Likewise, it recognizes that within the domain of what is permissible according to the normal rules of grammar, the expected representation may be abandoned in the interest of subtler considerations. This study also looks at the interpretation of the Qur'an by al-Zamakhshari, a passionate proponent of baIaghah in the domain of tafsir, or interpretation.